Engineering a selective fluorescent sensor with a high signal-to-background ratio for microalbumin detection and imaging. (14th September 2022) - Su, Liang; Yang, Feiyu; Li, Wei; Li, Haiyan; Wang, Chunjiang; Wang, Qiuan; Yuan, Lin
Abstract : A selective fluorescent sensor FNE3 with a high signal-to-background ratio was constructed for microalbumin quantitative detection and drug visualization. Abstract : Abnormal concentrations of human serum albumin (HSA) are closely related to the occurrence of various diseases, such as liver cirrhosis and kidney disease. Thus, it is of great importance to monitor HSA in body fluids, especially microalbumin in urine. However, due to the interference of other proteins and the low-polar microenvironment, a high signal-to-background (S/B) ratio and selective detection of microalbumin are still a great challenge. To this end, we propose an innovative strategy based on the two-pronged effect of the twisted intramolecular charge transfer (TICT) and the excited state intramolecular proton transfer (ESIPT) mechanisms of flavonoid fluorophores, which is used to significantly improve the signal-to-background ratio of the HSA selective fluorescent sensor. As a proof of strategy demonstration, an HSA specific binding flavonoid molecule (FNE3 ) was developed by combining chemical design and screening approaches. Due to binding to the new binding site (subdomain IB) of HSA in molecular simulations, FNE3 exhibits a remarkable 1042-fold fluorescence response for HSA but only a 1.8-fold for BSA, which has been the highest S/B ratio among HSA probes so far, enabling highly sensitive differential detection of HSA from other proteins. Moreover, FNE3 is superior to the commercial BCG method in the rapid and sensitive detection of microalbumin in clinical urine samples, and the quantitative detection results were in good agreement with the clinical data. With the excellent performance of FNE3, we further applied it to the selective detection of HSA-specifically bound drugs via a competitive displacement mechanism, and successfully realized the selective visualization of anti-inflammatory drugs diflunisal (DIF) in urine and living cells for the first time. This study indicates that FNE3 may offer a promising tool for the future HSA associated clinical testing and noninvasive pharmaceutical screening.